2021
DOI: 10.1155/2021/6688521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Location of Dental Mini-Implants on Strain Distribution under Mandibular Kennedy Class I Implant-Retained Removable Partial Dentures

Abstract: Purpose. To investigate the effect of minidental implant location on strain distributions transmitted to tooth abutments and dental minidental implants under mandibular distal extension removable partial denture. Materials and Methods. A mandibular Kennedy Class I distal extension model missing teeth 35–37 and 45–47 was constructed. Six dental mini-implants were placed at positions A, B, and C, where position A was 6.5 mm distal to the abutment teeth with 5 mm between each position. Fourteen uniaxial strain ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 30 publications
(36 reference statements)
2
22
0
Order By: Relevance
“…The thickness of artificial PDLs was 0.3 mm [ 32 ]. The conventional cobalt-chrome-molybdenum RPD framework, with lingual bar and rest-proximal plate-Akers (RPA) clasp engaged mesial undercut of both first premolar abutment teeth, was fabricated in the model [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness of artificial PDLs was 0.3 mm [ 32 ]. The conventional cobalt-chrome-molybdenum RPD framework, with lingual bar and rest-proximal plate-Akers (RPA) clasp engaged mesial undercut of both first premolar abutment teeth, was fabricated in the model [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Eight models of mini dental implant-assisted mandibular Kennedy class I bilateral distal extension RPD were generated by 6.13 ABAQUS program (ABAQUS 6.13, Simulia, Providence, RI, USA) with different numbers and locations of mini dental implants ( Figure 1 ). Mini dental implants were placed at second premolar, first molar, and second molar position distally from abutment tooth 6.5, 11.5, and 16.5 mm, respectively [ 33 ]. The measurement from a strain gauge model under the same conditions was utilized to validate the 3D FEA model at the surface area of FE model.…”
Section: Methodsmentioning
confidence: 99%
“…Two identical chemical-cured resin acrylic mandibular models with preformed resin teeth (PE-ANA002 ® ; Nissin, Kyoto, Japan) from 34 to 44 and bilateral distal extension edentulous ridges were fabricated. For the model assigned for FEA model fabrication, the polyvinyl siloxane (GI Mask Automix, Coltene, Madrid, Spain) was used to simulate the 2 mm gingival mucosa covered on edentulous ridges with an average of 0.3 mm periodontal ligament surrounded on the root surface of abutment teeth as described by a previous study (Figure 1(a)) [22]. e second model was prepared as a master model for framework fabrication.…”
Section: Methodsmentioning
confidence: 99%
“…To overcome this problem, the dental implant with smaller diameter called mini dental implants (MDIs) has been developed and applied. e success of using MDIs to gain the stability and retention of overdentures in patients who had compromised supporting bone has been addressed in previous studies [19][20][21][22][23]. However, Holmgren [24] found that the decrease in the bone-implant interface in case of MDIs resulted in higher and wider stress distribution in the peri-implant bone.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, digital technologies have been integrated into implant dentistry for prosthetic restoration rehabilitation of missing teeth [ 1 , 2 , 3 , 4 ]. For implant components, titanium (Ti) and its alloys are commonly used but they have disadvantages of causing black coloration in the anterior zone and causing allergy [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%